Development of an irreversible hydrochromic ink for smart packaging: DOI 10.14622/JPMTR-2004 - Bilgin, Mustafa; Backhaus, Johannes (Journal of Print and Media Technology Research, 2020)
Smart materials are based on chemical-physical processes that react to environmental factors or a specific stimulus. These factors or a predefined stimulus lead to structural changes. In this way, several smart materials can react to various influences such as temperature, UV light, or other. Smart materials of the type of hydrochromic inks change their colour under the influence of water or humidity. This stimulus-induced colour change process can occur in either reversible or irreversible form. Irreversible hydrochromic inks are preferable for a significant indication of the influence of water or moisture. Therefore, this research project focuses on the development and investigation of an irreversible hydrochromic ink for piezoelectric inkjet printing. For this purpose, the theoretical aspects of the chemical compound are discussed and the concept behind an irreversible hydrochromic ink is introduced. Several concentrations are evaluated and characteristic properties like viscosity, surface tension, particle size, and character-istic remission are analysed.